2018
DOI: 10.3389/fpsyg.2018.00182
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Modulates Neural Responses to Unfairness in the Ultimatum Game

Abstract: The current functional MRI study aimed to investigate how responders’ fairness considerations and related decision-making processes were affected by social support in the ultimatum game (UG). During scanning, responders either played the standard UG with proposers (control condition) or played the modified UG in which three unknown observers showed social support for responders by acknowledging proposers’ norm violation. Results revealed that participants reported higher unfairness feelings and rejection rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…To motivate the participants' choices, they were told that at the end of the experiment, one of the trials in which they accepted the offer would be selected randomly by the computer and that they would be paid based on that trial. This experimental design is commonly used in UG research (Gaertig et al, 2012 ; Wei et al, 2018 ; Pei et al, 2021 ). We also verbally asked the participants whether they had any questions about the content of the experiment and no one reported that they had doubts about the cover story.…”
Section: Methodsmentioning
confidence: 99%
“…To motivate the participants' choices, they were told that at the end of the experiment, one of the trials in which they accepted the offer would be selected randomly by the computer and that they would be paid based on that trial. This experimental design is commonly used in UG research (Gaertig et al, 2012 ; Wei et al, 2018 ; Pei et al, 2021 ). We also verbally asked the participants whether they had any questions about the content of the experiment and no one reported that they had doubts about the cover story.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 27 healthy, right-handed college students (14 males; 22.71 ± 2.64 years old, range: 18-30 years old) with no history of neurological or psychiatric disorders were recruited in this study from Beijing Normal University, China. Our sample size was determined empirically and was comparable with previous brain imaging studies using the UG (e.g., Guo et al, 2014;Halko et al, 2009;Hu et al, 2016;Sanfey et al, 2003;Wei et al, 2018). The study was conducted in accordance with the Declaration of Helsinki and approved by the Ethics Committee of Beijing Normal University.…”
Section: Participantsmentioning
confidence: 99%
“…)、焦 虑 Layte, 2011), 以 及 愤 怒 (Gummerum et al, 2016;Seip et al, 2014)等情绪, 降低幸福感和生活满意度 (Cheung & Lucas, 2016)。 在人际方面, 不公平经历会降低个体对他人的信任 (Fairbrother & Martin, 2013;Hastings, 2018), 减少 利他与合作行为 (Wu et al, 2015), 增加欺骗行为 (Houser et al, 2012;Valle & Ploner, 2017)和对不公 平实施者的攻击和报复行为 (Brosnan & de Waal, 2014;Brüne et al, 2013;Fehr & Fischbacher, 2004;Greitemeyer & Sagioglou, 2017;Henrich et al, 2006)。然而, 以往研究大多着重于考察个体"独自 经历"不公平时的认知、 情绪及行为, 而鲜有研究考 察"共同经历"不公平对个体的影响。 最 后 通 牒 博 弈 (Ultimatum Game, 简 称 UG) (Güth et al, 1982)和独裁者博弈(Dictator Game, 简 称 DG) (Kahneman et al, 1986)是用来考察不公平 现象的经典研究范式。在最后通牒博弈中, 两名参 与 者 分 别 被 赋 予 " 提 议 者 (proposer)" 或 " 接 受 者 (receiver)"的角色。由提议者对一笔资源(例如金钱) 进行分配。提议者提出分配方案, 接受者有权选择 "接受"或"拒绝"该方案。如果接受者选择"接受", 则按该分配方案进行分配; 如果接受者"拒绝", 则 提议者和接受者什么都得不到 (Inaba et al, 2018;Wei et al, 2018 Peterburs et al, 2017;Fehr & Fischbacher, 2004;Johanna et al, 2012) (Hu et al, 2015;Hu et al, 2014;Wu et al, 2011 (Brown et al, 1992;Leach & Vliek, 2008;Major et al, 1993;Smith & Leach, 2004)。毕竟, 只有当两件事情属于同一个类 Allport, 1940;Sherif & Hovland, 1961) Ding et al, 2017;Sawaoka et al, 2015;Wu et al, 2012) 更具竞争性和攻击性 (Insko et al, 1998;Jaffe & Yinon, 1979;Meier & Hinsz, 2004;…”
unclassified